2022
DOI: 10.1371/journal.pgen.1010131
|View full text |Cite
|
Sign up to set email alerts
|

BmPMFBP1 regulates the development of eupyrene sperm in the silkworm, Bombyx mori

Abstract: Sperm deliver the male complement of DNA to the ovum, and thus play a key role in sexual reproduction. Accordingly, spermatogenesis has outstanding significance in fields as disparate as infertility treatments and pest-control, making it a broadly interesting and important focus for molecular genetics research in a wide range of species. Here we investigate spermatogenesis in the model lepidopteran insect Bombyx mori (silkworm moth), with particular focus on the gene PMFBP1 (polyamine modulated factor 1 bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…As mutation of BmPrmt5 does not affect the production or stability of BmVasa, we speculate that BmPrmt5-mediated sDMA modification of BmVasa activates BmVasa allowing it to regulate spermatogenesis. We therefore propose Previous studies have demonstrated that morphology defects in the bundles of either eupyrene or apyrene sperm compromise their physiological function [10,11,14,19,20]. In BmPrmt5 and BmVasa mutants, there are severe defects in both sperm morphs.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…As mutation of BmPrmt5 does not affect the production or stability of BmVasa, we speculate that BmPrmt5-mediated sDMA modification of BmVasa activates BmVasa allowing it to regulate spermatogenesis. We therefore propose Previous studies have demonstrated that morphology defects in the bundles of either eupyrene or apyrene sperm compromise their physiological function [10,11,14,19,20]. In BmPrmt5 and BmVasa mutants, there are severe defects in both sperm morphs.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have demonstrated that morphology defects in the bundles of either eupyrene or apyrene sperm compromise their physiological function [ 10 , 11 , 14 , 19 , 20 ]. In BmPrmt5 and BmVasa mutants, there are severe defects in both sperm morphs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant F 1 progeny expressed both Cas9 and sgRNAs, causing DNA lesions in BmDicer1, resulting in independent de novo mutations in each of the cross's offspring. Thus, we referred to the mosaic mutagenesis of the mutant as "somatic" (Zhang et al, 2017;Yang et al, 2022). Genomic DNA from day 2 of the 3rd instar larvae was used as a template for PCR-based analysis.…”
Section: Bmdicer1 Mutagenesis Using the Crispr/cas9 Systemmentioning
confidence: 99%
“…The final product of this deliberate and orchestrated process is two morphs with different morphologies made with different proteomes, comprising some shared proteins and some proteins unique to one or other morph (9, 10). A small number of genes have been demonstrated via CRISPR-Cas9/RNAi experiments to be important for Lepidopteran sperm heteromorphism, including Sex-lethal (Sxl) (Table S1) (5, 6, 11, 12). However, there has not been a systematic, unbiased identification of differentially expressed genes that ensure normal differentiation of spermatocytes towards eupyrene and apyrene sperm fates.…”
Section: Introductionmentioning
confidence: 99%